lab9_solns_f11

lab9_solns_f11 - Math 116 - Lab 9 Solutions - Fall 2011. 1....

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 116 - Lab 9 Solutions - Fall 2011. 1. Compute the following integrals by substitution. a) I = integraltext sin(3 x ) dx . We can use the substitution u = 3 x , which gives du = u ′ ( x ) dx = 3 dx and thus du/ 3 = dx , so I = integraltext sin( u ) / 3 du =- cos( u ) / 3 + c =- cos(3 x ) / 3 + c . b) I = integraltext exp( t + 3) dt . We can use the substitution u = t + 3, which gives du = u ′ ( t ) dt = dt , so I = integraltext exp( u ) du = exp( u ) + c = exp( t + 3) + c . c) I = integraltext (3 t 3 + 7) 4 t 2 dt . We can use the substitution u = 3 t 3 + 7, which gives du = u ′ ( t ) dt = 9 t 2 dt and thus du/ 9 = t 2 dt , so I = integraltext u 4 / 9 du = u 5 / 45 + c = (3 t 3 + 7) 5 / 45 + c . d) I = integraldisplay t 3 t 2 + 5 dt . We can use the substitution u = 3 t 2 + 5, which gives du = u ′ ( t ) dt = 6 tdt and thus du/ 6 = tdt , so I = integraltext 1 / (6 u ) du = 1 / 6 ln | u | + c = 1 / 6 ln | 3 t 2 + 5 | + c . e) I = integraldisplay 3 x 2 1 + x 6 dx . (Hint: recall the derivative of arctan( x ).) We can use the substitution u = x 3 , which gives du = u ′ ( x ) dx = 3 x 2 dx , so I = integraltext 1 / (1 + u 2 ) du = arctan( u ) + c = arctan( x 3 ) + c . f) I = integraldisplay 1 t 2 + 2 t + 5 dt . (Hint: recall the derivative of arctan( x ) and complete the square.) Upon inspection, it looks like this integral may fit the pattern of integrating the derivative of arctan( x ), if we manage to complete the square in the denominator of the integrand. Completing the square we get: I = integraldisplay 1 t 2 + 2 t + 1- 1 + 5 dt = integraldisplay 1 ( t + 1) 2 + 4 dt = 1 4 integraldisplay 1 (( t + 1) / 2) 2 + 1 dt, so we can use the substitution u = ( t +1) / 2, which gives du = u ′ ( t ) dt = 1 / 2 dt and thus 2 du = dt , so...
View Full Document

This note was uploaded on 12/28/2011 for the course MATH 116 taught by Professor Robertandre during the Spring '11 term at Waterloo.

Page1 / 3

lab9_solns_f11 - Math 116 - Lab 9 Solutions - Fall 2011. 1....

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online